Multifractal Detrended Fluctuation Analysis of the Chinese Stock Index Futures Market - Xinsheng Lu; Jie Tian; Ying Zhou; Zhihui Li (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2012)
Based on the multifractal detrended fluctuation analysis (MF-DFA) and multifractal spectrum analysis, this paper empirically studies the multifractal properties of the Chinese stock index futures market. Using a total of 2,942 ten-minute closing prices, we find that the Chinese stock index futures returns exhibit long-range correlations and multifractality, making the single-scale index insufficient to describe the futures price fluctuations. Further, by comparing the original time series with the transformed time series through shuffling procedure and phase randomization procedure, we show that there exists two different sources of the multifractality for the Chinese stock index futures market. Our results suggest that the multifractality is mainly due to long-range correlations, although the fat-tailed probability distributions also contribute to such multifractal behavior.
Keywords: 330; Multifractality; Stock index futures; MF-DFA; Generalized Hurst exponent